(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study of world practice shows that small business occupies one of the first places in the ranking of economic priorities, in connection with which there is a harmonious system of its investment support aimed at stimulating innovative content, both of the business itself and entrepreneurs. Noting the advantages of small businesses, such as flexibility, low operating costs, and high capital turnover, the most important thing should be highlighted - the formation of innovative thinking and behavior. A free, creative person is allowed to embody his ideas.